A field test for ferrous iron and ferric-organic complexes in cerrados soils - Cochrane, Thomas T.; Sousa, Djalma M. G. de (Pesquisa Agropecuaria Brasileira, 2014)
A 0.1 M solution of barium chloride containing 1,10 - phenanthroline indicator gave a satisfactory field test for exchangeable and water-soluble ferrous iron in Cerrados soils. A 1 ml subsample of soil is added to a vial containing 5 ml of the solution and shaken for 20 seconds. An orange-red colour indicates the presence of ferrous iron. The presence of ferric-organic complexes in soils can also be detected, as the reduction of ferric to ferrous iron in the presence of oxidisable organic ligands is a photochemical process. Subsamples of soils are added to two separate vials containing the solution and shaken for 20 seconds. One vial is kept in the dark and the other exposed to sunlight. After five to fifteen minutes, the development of an orange-red colour in the vial exposed to light in contrast with no colour change in the other, indicates the presence of ferric-organic complexes.